Acute left arm ischemia after TEVAR due to the anatomical variation of the vertebral artery : case report = Akutna ishemija lijeve ruke nakon TEVAR-a zbog anatomske varijante vertebralne arterije : prikaz slučaja - Figl, Josip (Array, 2021)
Aim: In this case we report acute left arm ischemia after thoracic endovascular aortic repair of the saccular thoracic aortic aneurysm due to a rare anatomical variation of the left vertebral artery. Case report: Thoracic aortic stent-graft was deployed to cover the aneurysm, but six hours later acute left arm ischemia occurred due to a rare form of vertebral artery origin from the aortic arch instead of from the left subclavian artery. This hostile anatomy led to an iatrogenic acute ischemia which was the indication for an emergency left-common-carotid-to-subclavian-artery bypass grafting. Conclusion: Multidisciplinary approach and careful pre-procedural planning should always be the standard procedure in complex cases to avoid this complication.